Purely elastic instabilities in three-dimensional cross-slot geometries - A. M. Afonso (2010)
Creeping and low Reynolds number flows of an upper-convected Maxwell (UCM) fluid are investigated numerically in a three-dimensional orthogonal cross-slot geometry. We analyze two different flow configurations corresponding to uniaxial extension and biaxial extension, and assess the effects of extensional flow type, Deborah and Reynolds numbers on flow dynamics near the interior stagnation point. Using these two flow arrangements the amount of stretch and compression near the stagnation point can be varied. providing further insights on the viscoelastic flow instability mechanisms in extensionally dominated flows with an interior stagnation point. The uniaxial extensional flow arrangement leads to the onset of a steady flow asymmetry, followed by a second purely elastic flow instability that generates an unsteady flow at higher flow rates. On the other hand, for the biaxial extension flow configuration a symmetric How is observed up to the critical Deborah number when the time-dependent purely elastic instability sets in, without going through the steady symmetric to steady asymmetric transition.